The Role of Hematopoietic Stem Cell Transplantation for Pediatric Relapsed or Refractory Non-Hodgkin's Lymphoma: Results of the Turkish Pediatric Bone Marrow Transplantation Study Group - Hazar, V.; Kesik, V.; Karasu, G. Tezcan; Ozturk, G.; Kupesiz, A.; Kilic, S. Caki; Yesilipek, A. (Nature Publishing Group, 2016)
…
42nd Annual Meeting of the European-Society-for-Blood-and-Marrow-Transplantation -- APR 03-06, 2016 -- Valencia, SPAIN